STRENGTHENING THE CHARACTER EDUCATION BASED ON SYED M. NAQUIB AL-ATTAS (A CASE OF STUDY OF AL-ISHLAH CIBINONG JUNIOR HIGH SCHOOL) - Merri Yulia Muchlasin; Galih Pratama Pratama; Akhmad Alim (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
The aim of National education is to create a generation that has good character and noble character. But 8 of 10 children experienced bullying cases in Indonesia stay on 4th in cases of child abuse. Syed Muhammad Naquib Al-Attas as an educational figure in contemporary Islamic times. This study uses qualitative research methods with the type of library research. Strengthening Education forms good human character, Syed M. Naquib Al-Attas uses the concept of ta'dib, which is to instill good manners to form praiseworthy personalities in humans that encompass habits, character and habits. Strengthening character education at Al-Ishlah Cibinong Junior High School based on the Qur'an in planning, management, implementation and evaluation. Strengthening character education is highly needed in junior high schools by applying the model model, learning in class, integrating with all subject matter, integrating in Intrakulikuler, Kokurikuler and Extracurricular activities, empowerment and coaching.